2005
DOI: 10.1007/s10151-005-0185-6
|View full text |Cite
|
Sign up to set email alerts
|

Stoma formation for fecal diversion: a plea for the laparoscopic approach

Abstract: The advantages of laparoscopic stoma creation are low morbidity and reoperation rates, and no procedure-related mortality; our results suggest that laparoscopic stoma creation for fecal diversion is safe, feasible and effective. Therefore, at our institution, laparoscopic stoma creation is the method of choice for fecal diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 21 publications
2
29
0
4
Order By: Relevance
“…Without exception, all these studies concluded that the laparoscopic approach to the creation of a stoma is reliable, technically feasible and effective [1,2,6]. In particular, when the stoma is applied as the sole abdominal intervention, the laparoscopic approach appears to be a very good option [1,3].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Without exception, all these studies concluded that the laparoscopic approach to the creation of a stoma is reliable, technically feasible and effective [1,2,6]. In particular, when the stoma is applied as the sole abdominal intervention, the laparoscopic approach appears to be a very good option [1,3].…”
Section: Discussionmentioning
confidence: 98%
“…In view of this fact, a surgical approach associated with a minimum of traumatization would appear especially desirable in these patients [3,4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, laparoscopic techniques have been adopted for various surgeries, including stoma creation. Since Khoo et al 7) first reported the technique of laparoscopic loop ileostomy, many less invasive techniques for stoma creation, including SILS and gasless LS creation, have been described [8][9][10][11][12][13][14] . In this study, we analyzed data from patients who underwent stoma creation and discussed the indications for the surgical approaches used.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy has been described as the best way to proceed for the formation of an intestinal stoma (17,18). In the gasless technique, there are no incisions other than the one that is done to create the stoma.…”
Section: Discussionmentioning
confidence: 99%